Severe knee injuries among karate athletes ranking towards the Tokyo Olympic Games: a retrospective study - Pérez-Martín, L.; Augustovicova, D.; Martínez-de-Quel, Ó.; Tabben, M.; Arriaza, R. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: Injury prevention strategies should be built upon data about the more frequent injuries in each specific sport. Therefore, this study aimed to describe the lifetime prevalence and characteristics of severe knee injuries among world-class karatekas. METHODS: A retrospective study based on a face-to-face survey was conducted. Participants were athletes who competed in World Karate Senior Championships in Madrid 2018, which was a tournament with the highest value to rank athletes to the Tokyo Olympic Games. A questionnaire was used to collect retrospective information on the prevalence and characteristics of severe knee injuries that occurred along elite karatekas sport careers. Odds Ratio (OR) were calculated to identify the association of sex and karate modality (kata / kumite) with severe knee injury risk. RESULTS: Out of the 293 athletes surveyed (23.4±4.0 years; 137 female), 71 (24.2%) had suffered a serious knee injury at some point of their careers, without a statistically significant difference between male and female athletes. There was no difference between the percentage of injuries that took place during training (54.9%) or during competition (45.1%) both in male and female athletes. Kumite athletes suffered more knee injuries during competition than training. The most common injury mechanism for both genders was a pivoting or dodging movement (36.4% in males and 39.5% in females). CONCLUSIONS: The information presented in this study about the prevalence and characteristics (mechanism, anatomical location, moment, time off) of the severe knee injuries in elite karatekas could be useful to design prevention programs to be implemented among karate athletes.